Integrating Visual Thinking of Hearing Impaired Students in Inclusive Classroom - Ama liyah; Fajar Syarif (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Education in inclusive classes is a national alternative program in the context of fulfilling education rights based on a non-discriminatory spirit. However, in the implementation of education, there are problems that students with disabilities have in the difficulties of getting an inclusive school that meets their needs. Even schools that are considered inclusive can only fulfill 5% of the obligations required by the government for disabled students, without the provision of adequate facilities and infrastructure, and only students with disabilities who have moderate or mild disabilities can be educated in these inclusive schools. The method in this research uses qualitative research with basic research in the form of analyzing the principles in education, therefore this research is not directly useful in practice but takes time to see the results. This study also uses primary and secondary data sources, and data collection techniques by observation, in-depth interviews, documentation and research instruments. While the data analysis technique uses qualitative explorer, triangulation, and content analysis. The first finding of the research shows that visual thinking is a method that can facilitate hearing impaired students in learning Islamic education in full regular inclusive classes. This is evidenced from the academic achievement of hearing impaired students, including the ability to remember, the ability to think, the ability to find solutions, the ability to express opinions. The second finding shows that integrating visual thinking method that implements students' needs through the approach of the collaboration visual thinking method and the visual thinking strategies approach, as learning solutions that move students actively as subjects and objects of learning. Keywords: Integrating Visual Thinking, hearing impaired students, Inclusive Education